2023
DOI: 10.1002/smll.202301731
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Dealloyed 3D Porous Copper Nanostructure as Anode Current Collector of Li‐Metal Batteries

Abstract: The commercialization of high-energy Li-metal batteries is impeded by Li dendrites formed during electrochemical cycling and the safety hazards it causes. Here, a novel porous copper current collector that can effectively mitigate the dendritic growth of Li is reported. This porous Cu foil is fabricated via a simple two-step electrochemical process, where Cu-Zn alloy is electrodeposited on commercial copper foil and then Zn is electrochemically dissolved to form a 3D porous structure of Cu. The 3D porous Cu la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…At a charge–discharge rate of 5C (Figure a), the specific capacities of MC–MA and CC–CA are 382 and 367 mAh/g, and capacity retention rates are 84.84 and 81.85%, respectively. The slight increase in capacity in the initial stage is attributed to the gradual activation process . When the cycle test rate increases to 10C (Figure b), the specific capacity of MC–MA is 342.3 mAh/g, and the capacity retention rate is 76.96%; the specific capacity of CC–CA is 277.5 mAh/g, and the capacity retention rate is 62.43%.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…At a charge–discharge rate of 5C (Figure a), the specific capacities of MC–MA and CC–CA are 382 and 367 mAh/g, and capacity retention rates are 84.84 and 81.85%, respectively. The slight increase in capacity in the initial stage is attributed to the gradual activation process . When the cycle test rate increases to 10C (Figure b), the specific capacity of MC–MA is 342.3 mAh/g, and the capacity retention rate is 76.96%; the specific capacity of CC–CA is 277.5 mAh/g, and the capacity retention rate is 62.43%.…”
Section: Resultsmentioning
confidence: 96%
“…The slight increase in capacity in the initial stage is attributed to the gradual activation process. 34 When the cycle test rate increases to 10C (Figure 7b), the specific capacity of MC−MA is 342.3 mAh/g, and the capacity retention rate is 76.96%; the specific capacity of CC−CA is 277.5 mAh/g, and the capacity retention rate is 62.43%. The rapid capacity fading at a 10C rate is mainly attributed to the formation of lithium dendrites.…”
Section: Storage Stabilitymentioning
confidence: 98%
“…In the case of lithium metal batteries, interestingly, lithium also deposits on lithiophilic substrates, which tend to dissolve lithium partially or form an alloy with Li, like gold, even though they have an FCC lattice. Cu is among the least favourable substrates due to its reduced Li solubility and FCC structure [127,138,152]. Dealloying from Cu-Zn alloy has been reported using various metals, including chemical treatment [133], and vacuum distillation (due to the reduced vapour pressure of Zn) [132].…”
Section: Metallic Current Collectorsmentioning
confidence: 99%
“…Reducing the quality and thickness of current collectors can lower the weight percentage, thereby increasing the energy density of the battery. Nanomodification technology is currently widely applied in lightweight and thin current collectors. Ma et al reported a new type of porous copper current collector, which not only effectively slowed the lithium dendrite growth but also had an average thickness of approximately 14 μm and approximately 72% porosity. At 10 mA cm –2 and an areal capacity of 10 mA h cm –2 , cells with a porous Cu current collector could still deliver good cycling stability up to 230 h. Chen et al reported an integrated bidirectional porous Cu (IBP-Cu) current collector with tunable pore volume and size that exhibited high mechanical flexibility and stability, and the Li|IBP-Cu-based symmetric cell exhibited a low and stable polarization voltage of 46 mV for over 4000 h at 1.0 mA cm –2 and 1.0 mAh cm –2 .…”
Section: Current Collectormentioning
confidence: 99%
“…Impressively, the Li/IBP-Cu anode as-fabricated demonstrates an ultralong cycling ability with high Coulombic efficiency of about 100% for 1000 cycles, amazing rate performance, and extraordinary capacity of up to 7.0 mA h cm −2 for deep plating/stripping. Chen and co-workers 56 reported a new type of porous copper collector that can effectively slow down the dendritic growth of lithium. This porous copper foil is manufactured through a simple two-step electrochemical process, where a Cu−Zn alloy is electrodeposited on commercial copper foil, and then Zn is electrochemically dissolved to form a 3D porous structure of Cu.…”
Section: Current Collectormentioning
confidence: 99%